Chicken IL-17 as a potent adjuvant enhances IBDV VP2 DNA vaccine immunogenicity and protective efficacy - Jianlou Zhang; Wenyan Li; Shanshan Huo; Xiaojing Xin; Liyue Wang (Poultry Science)
Infectious bursal disease virus (IBDV) is an important immunosuppressive virus in chickens, which caused an acute and highly contagious infectious disease and resulted in considerable economic losses in the world poultry industry. Although IBDV VP2 DNA vaccine has been extensively proved only partial protection, the efficacy of DNA vaccines against IBDV can be augmented by choosing potential molecular adjuvants. To investigate whether chicken IL-17 (chIL-17) is qualified for the molecular adjuvant, we constructed chIL-17 gene vector, co-immunized chickens with chIL-17 gene vector and IBDV VP2 DNA vector, and analyzed the effect of IL-17 gene on the immunogenicity of VP2 DNA vaccine. Results showed that co-administrated chIL-17 gene and VP2 DNA vaccine significantly increased IBDV-specific serum antibody titer, and promoted lymphocyte proliferation and interference-γ (IFN-γ) production. Mechanically, chIL-17 reduced virus titer in bursa of fabricius tissue and mortality of IBDV-infected chicken. More importantly, chIL-17 gene significantly enhanced the protection induced by the VP2 gene against virulent IBDV infection.These data show that chIL-17 is a promising immunoadjuvant to facilitate humoral as well as cellular immunity in a vaccine setting against IBDV, and suggest that it should be evaluated as a new DNA vaccine adjuvant in strategies for other poultry diseases.